MOPNITORING OF MORPHO-FUNCITONAL INDICES OF QUALIFIED PLAYERS SPECIALIZING IN RUGBY-7 (Physical Culture and Sport: Scientific Perspective, 2023)
The paper presents research focused on the process of athletes training specializing in rugby-7. Current research outcomes enable to state that such morphological indices as body frame, body weight and composition are important components of evaluation of athletes’ preparedness to competition as well as to being selected to a sports team. The aim of the article lies in theoretical and experimental research of morphological indices significance of “Podillya” (Khmelnytskyi) rugby players as an informative index of training process management for players at various positions in rugby-7. To achieve the aim, pedagogical analysis of athletes’ anthropometric indices and body weight has been done. Instrumental methods to define body composition using bioimpendence method and “TANITA–RD545” smart scales were used. 12 leading athletes of “Podillya” (Khmelnytskyi) team took part in the research. The research has revealed differences related to anthropometric indices of team players depending on their positions – players on offense are usually higher and weight more compared to defenders. At the same time, morphological indices obtained during athletes testing prove that body weight index (BWI) is within physiological norm of 86% of athletes; with 14% of athletes this index slightly exceeds physiological norm.  Analysis of rugby players’ body composition proves that the content of fatty tissue was higher with forwards but it was within physiological norm in accordance with anthropometric data of athletes or was approximated to the highest point. The content of muscle tissue was statistically higher with forwards. All athletes had water content within physiological norm. Our research has revealed that higher weight of forwards was accompanied with a higher content of body fat. It should be noted that percentage of fatty weight of “Podillya” (Khmelnytskyi) rugby players was higher than the one of players of teams from New Zealand, Australia, and Spain. During the pedagogical research morphological indices significance for monitoring of the state of athletes in rugby-7 depending on their positions  has been proven.
Keywords: morpho-functional indices; poistion; qualified rugby players; rugby-7